Comparative Approach of the Antibiotics Susceptibility of some Bacterial Strains Concurrently Isolated from Raw Milk and Cattle Feed (Water and Fodder) from some Farms in the West Region of Cameroon (Central Africa) - P. Ngo Bahebeck; C. S. Metsopkeng; J. S. Eheth; A. Tamsa Arfao; A. Manouore Njoya; Y. Poutoum Yogne; S. Lacmata Tamekou; H. Bayemi Pougue; O. V. Noah Ewoti; L. M. Moungang; P. A. Nana; E. Masseret; et al. (Archives of Current Research International, 2021)
Introduction: Foodborne resistant bacteria have become a challenge to food security. Milk and milk products are easy vectors of transmission of foodborne pathogens, these being the main sources of human infection by antimicrobial resistant pathogens. The present study aimed at making a comparative approach of the antibiotic sensitivity/resistance of 3 bacterial strains (Escherichia coli, Salmonella spp. and Brucella spp.) isolated from milk, drinking water and green fodder consumed by cows in the West Cameroon region (Central Africa). Methodology: A total of 48 raw milk samples, 48 water samples and 48 green fodder samples were collected during the year 2020 and subjected to culture and identification of Escherichia coli, Salmonella spp. and Brucella spp. Antibiotic susceptibility testing was performed using the antibiotic disc diffusion method. Results: Escherichia coli isolates showed high resistance (56-100%) to ampicillin, amoxicillin/clavulanic acid, cefotaxime, ceftazidime and ceftriaxone in all three samples. Salmonella spp. isolates showed resistance to ampicillin only (62, 67 and 67%). Brucella spp. strains isolated from raw milk and drinking water showed high sensitivity (78-100%) to azithromycin, doxycycline, ciprofloxacin, levofloxacin, gentamicin, rifampicin and trimethoprim/sulfamethoxazole, streptomycin and tetracycline. Antibiotic sensitivity/resistance to Escherichia coli and Salmonella spp. strains largely did not differ between samples (P>0.05). No difference in sensitivity/resistance (P>0.05) of Brucella spp. strains isolated from milk and water was observed with respect to the 10 antibiotics tested. Conclusions: The emergence of resistance to various antibiotics commonly used in medical and veterinary practices has important implications for public health. It seems necessary to strengthen of the regulations covering the sale and prescription of antibiotics.